A yeast genetic system for selecting small molecule inhibitors of protein–protein interactions in nanodroplets - Huang, Jing (The National Academy of Sciences of the USA, 1997)
Cellular processes are mediated by complex networks of molecular interactions. Dissection of their role most commonly is achieved by using genetic mutations that alter, for example, protein–protein interactions. Small molecules that accomplish the same result would provide a powerful complement to the genetic approach, but it generally is believed that such molecules are rare. There are several natural products, however, that illustrate the feasibility of this approach. Split-pool synthesis now provides a simple mechanical means to prepare vast numbers of complex, even natural product-like, molecules individually attached to cell-sized polymer beads. Here, we describe a genetic system compatible with split-pool synthesis that allows the detection of cell-permeable, small molecule inhibitors of protein–protein interactions in 100- to 200-nl cell culture droplets, prepared by a recently described technique that arrays large numbers of such droplets. These “nanodroplets” contain defined media, cells, and one or more beads containing ≈100 pmol of a photoreleasable small molecule and a controlled number of cells. The engineered Saccharomyces cerevisiae cells used in this study express two interacting proteins after induction with galactose whose interaction results in cell death in the presence of 5-fluoroorotic acid (inducible reverse two-hybrid assay). Disruption of the interaction by a small molecule allows growth, and the small molecule can be introduced into the system hours before induction of the toxic interaction. We demonstrate that the interaction between the activin receptor R1 and the immunophilin protein FKBP12 can be disrupted by the small molecule FK506 at nanomolar concentrations in nanodroplets. This system should provide a general method for selecting cell-permeable ligands that can be used to study the relevance of protein–protein interactions in living cells or organisms.